A field method for rapidly assessing deer density and impacts in forested ecosystems. (27th September 2021) - Bennett, Ami; Fedrigo, Melissa; Greet, Joe
Summary: Overabundant deer populations can cause severe ecological impacts. To inform management decisions and assess the effectiveness of mitigation strategies, land managers require a rapid and cost‐effective method for collecting data on both deer density and impacts. Here, we describe a field method for rapidly and concurrently assessing indices of deer density and impacts in forested habitats, and using field data collected in 2019–2020, we demonstrate its performance. The method combines commonly used protocols for surveying deer faecal pellets, vegetation impact and floristic attributes, without relying on indicator species. The survey involves assessment of 150‐m transects in forested habitats along which 30 plots are surveyed for faecal pellets of deer and sympatric herbivores (here, Swamp Wallaby, Wallabia bicolor ), and impacts on woody trees and shrubs at different heights. In total, we surveyed 154 transects comprising 15, 941 plant impact assessments and assessed the methods performance using basic and comparative statistics, and power analyses. Almost all plant species were similarly impacted at the local (transect) level. Indices of deer and Swamp Wallaby density explained similar amounts of variance in impacts <1 m, while the deer index explained much more of the variance in impacts >1 m. We detected differences in vegetation impact and other floristic attributes between four locations surveyed in 2020 from a modest sample size (23–24 transects). The method is simple to implement and can be applied in a wide range of forest types. In comparison to alternatives (e.g. fenced exclosures), this method presents a rapid and cost‐effective means of collecting information on deer density and impacts, and detecting large differences in impact. We suggest that the proposed method enables rapid landscape‐scale assessments of deer impacts suitable for evaluating management interventions.